2012
DOI: 10.1142/s2010194512005855
|View full text |Cite
|
Sign up to set email alerts
|

Quark-Cluster Stars: Hints From the Surface

Abstract: The matter inside pulsar-like compact stars could be in a quark-cluster phase since in cold dense matter at a few nuclear densities (ρ ∼ 2 − 10ρ 0 ), quarks could be coupled still very strongly and condensate in position space to form quark clusters. Quark-cluster stars are chromatically confined and could initially be bare, therefore the surface properties of quark-cluster stars would be quite different from that of conventional neutron stars. Some facts indicate that a bare and self-confined surface of pulsa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…We find that the maximum mass of quark-cluster stars can be well above 2M . Although, in principle, one may obtain a maximum mass high enough to explain observations in any kinds of unphysical models, we call attention to the point that the quark-cluster star model has meaningful implications for one to understand different manifestations, such as of the surface [17]. Additionally, the melting heat is also discussed, and it is shown that the solidification of newly born quark-cluster stars might explain the plateau of γ-ray bursts.…”
Section: Introductionmentioning
confidence: 99%
“…We find that the maximum mass of quark-cluster stars can be well above 2M . Although, in principle, one may obtain a maximum mass high enough to explain observations in any kinds of unphysical models, we call attention to the point that the quark-cluster star model has meaningful implications for one to understand different manifestations, such as of the surface [17]. Additionally, the melting heat is also discussed, and it is shown that the solidification of newly born quark-cluster stars might explain the plateau of γ-ray bursts.…”
Section: Introductionmentioning
confidence: 99%
“…随着核反应实验的进展, Bethe 提出了 氢核聚变成氦核的 CNO 循环机制 [7] . 由此看来, 关 于恒星能源问题, Landau(1932) [26][27][28][29] . 过去一些相关研究归纳如下.…”
Section: Landau 犯下这第二个错误是因为当时未发现强 相互作用 强相互作用至少会为大原子核研究带来 两方面的重要影响unclassified
“…Phenomenologically, some observations may hint that a bare and self-confined surface might exist in order to naturally understand different observational manifestations (e.g., sub-pulse drifting, a non-atomic spectrum, and clean fireballs for supernova/𝛾-ray bursts). [2] It is expected that because of the low temperature gradient of a surface with degenerate electrons, the linear polarization of thermal x-ray emissions from quark-cluster stars will be very low, [3] however, a quantitative calculation has never been presented. In this Letter, we calculate the polarization behavior of quark-cluster stars and compare our results to the pre-existing conclusion of neutron stars [4] in order to test pulsar structure models by future advanced x-ray polarimetries.…”
mentioning
confidence: 99%